Process for improving oxygen ring defect

By adjusting the heat shield position and using specific impurity removal processes, the process addresses oxygen ring defects in Czochralski single crystals, reducing thermal stress and dislocation generation to improve crystal quality.

CN119121379APending Publication Date: 2024-12-13HONGYUAN NEW MATERIAL BAOTOU CO LTD +1
View PDF 0 Cites 1 Cited by

Patent Information

Application Number
CN202411282457.6
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-09-13
Publication Date
2024-12-13

AI Technical Summary

Technical Problem

Oxygen ring defects in Czochralski single crystals are formed due to the nucleation and growth of oxygen precipitates, leading to excess stacking faults and thermal stress, which existing processes fail to effectively address.

Method used

A process involving the adjustment of the heat shield position during crystal pulling, combined with argon gas flow and subsequent heat treatments, to control the temperature gradient and reduce thermal stress, thereby reducing the formation of defects, and the use of specific impurity removal processes to enhance the quality of the growth of the crystal, and the use of specific impurity materials, and the use of specific impurities, and the use of specific impurity removal materials.

Benefits of technology

The process effectively reduces the formation of oxidation-induced stacking fault rings by controlling the solid-liquid interface V/G value and thermal stress, resulting in reduced dislocation generation and improved crystal quality.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119121379A_ABST
    Figure CN119121379A_ABST
Patent Text Reader

Abstract

The invention discloses a process for improving oxygen ring defects, and relates to the field of Czochralski single crystal manufacturing, the process comprises the following steps: S1, preparing a single crystal furnace: the single crystal furnace comprises a carbon felt, a quartz crucible, a graphite support, a solution, a heater, a heat shield, a crystal bar, a furnace body shell and an argon pipe; s2, crystal pulling treatment; s3, setting different liquid opening distances to produce crystal bars for small-batch battery verification, and monitoring the OSF generation condition after battery topcon high-temperature diffusion heat treatment; and S4, carrying out an oxygen precipitation heat treatment process and a Cu diffusion process on the material for impurity removal. According to the technology for improving the oxygen ring defect, the position of a heat shield is adjusted, monocrystalline silicon oxidation induced staggered rings are reduced, on the basis of the forming principle of the defect, the V / G value of a solid-liquid interface is controlled to be larger than the critical value of 0.13 mm < 2 > min <-1 > k <-1 > in the production process, and reduction of thermal stress is controlled; higher vacancy concentration can be obtained, dislocation can be reduced, and OSF-ring generation can be avoided.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the field of Czochralski single crystal manufacturing, and in particular to a process for improving oxygen ring defects. Background Art

[0002] Studies have shown that the oxygen content in the Czochralski single crystal is introduced into the silicon crystal at 1400℃ and exists in the form of interstitial oxygen. As the temperature decreases, the solid solubility of oxygen in the silicon crystal decreases, the interstitial oxygen precipitates, and the oxygen combines with the vacancy defect. As the temperature changes, the oxygen precipitate nucleates and grows: (1+r)SI+2Oi+βV (vacancy); SIO2+rSi I + Stress relief.

[0003] The nucleation center of OSF is a complex of oxygen precipitation and dislocation. The transformation from oxygen precipitation to OSF is achieved by stress-promoting supersaturation of interstitial silicon atoms. The oxygen precipitation grows and the large volume change causes silicon atoms to transfer away from the interface between the precipitation and the silicon matrix, forming excess stacking faults and finally forming OSF.

[0004] Therefore, it is necessary to propose a process to improve oxygen ring defects to solve the above problems. Summary of the invention

[0005] The main purpose of the present invention is to provide a process for improving oxygen ring defects, which can effectively solve the problems in the background technology.

[0006] To achieve the above object, the technical solution adopted by the present invention is: A process for improving oxygen ring defects, comprising the following steps: S1: Prepare the single crystal furnace: The single crystal furnace includes carbon felt, quartz crucible, graphite support, melt, heater, heat shield, crystal rod, furnace shell and argon gas pipe; S2: Crystal pulling process: Start the heater to heat the quartz crucible. After heating, the crystal rod is combined with the melt for crystal pulling. During the crystal pulling process, the heat shield is controlled to move so that the bottom of the heat shield is away from the melt surface, so that the y value of the crystal increases, which is used to increase the heat radiation area of ​​the side wall of the quartz crucible. The crystal is filled with argon through the argon gas pipe to increase the heating of the lower part of the crystal rod. S3: Set different liquid inlet distances to produce crystal rods for small-batch battery verification, and monitor the OSF generation after the battery topcon high-temperature diffusion heat treatment; S4: Performing oxygen precipitation heat treatment process and Cu diffusion process on the impurity removal materials: the materials include CZ-Si and NCZ-Si. The treated CZ-Si and NCZ-Si are ground with 800 mesh and 2000 mesh SiC particles, and then chemically polished with CP4 solution at 90°C for 30s. Al with a thickness of 30nm is deposited on the prepared crystal through mask deposition.

[0007] Preferably, in step S1, the carbon felt is placed at the bottom of the furnace body shell, the graphite tray is located on the top of the carbon felt, the quartz crucible is placed on the top of the graphite tray, the melt is placed in the inner cavity of the quartz crucible, the heater is installed on the outer wall of the quartz crucible, the heat shield is placed in the inner cavity of the quartz crucible, the crystal rod extends to the melt, the argon gas pipe is installed on the side of the furnace body shell, and the furnace body shell is also equipped with a thickened insulation barrel for reducing the power of seeding and equal diameter, reducing crucible baking, avoiding more oxygen precipitation, reducing the radial gradient, and reducing the thermal stress of the growth interface.

[0008] Preferably, the treatment of CZ-Si includes oxygen precipitation heat treatment process: 800℃ / 225h, Cu diffusion process: conventional diffusion, 1200℃ / 10min, air cooling; 800℃ / 225h, Cu diffusion process: RTP diffusion, 1200℃ / 50s; 800℃ / 225h+1250℃ / 2h, Cu diffusion process: conventional diffusion, 1200℃ / 10min, air cooling; 750℃ / 16h+1050℃ / 32h, Cu diffusion process: conventional diffusion, 1200℃ / 10min, air cooling; Diffusion process: conventional diffusion, 1000℃ / 10min, air cooling; 750℃ / 16h+1050℃ / 32h, Cu diffusion process: conventional diffusion, 1200℃ / 10min, air cooling; 750℃ / 16h+1050℃ / 32h, Cu diffusion process: RTP diffusion, 1000℃ / 50s, air cooling; 750℃ / 16h+1050℃ / 32h, Cu diffusion process: RTP diffusion, 1000℃ / 100s, air cooling.

[0009] Preferably, the treatment of NCZ-Si includes oxygen precipitation heat treatment process: 800℃ / 225h, Cu diffusion process: RTP diffusion, 1200℃ / 50s; 800℃ / 225h+1250℃ / 2h, Cu diffusion process: conventional diffusion, 1200℃ / 10min, and air cooling.

[0010] Beneficial Effects Compared with the prior art, the present invention provides a process for improving oxygen ring defects, which has the following beneficial effects: 1. The process for improving the oxygen ring defect is a process for reducing the oxidation-induced stacking fault ring of single crystal silicon by adjusting the position of the heat shield. Based on the formation principle of this defect, the solid-liquid interface V / G value is controlled to be greater than the critical value of 0.13 mm during the production process. 2 min -1 k -1 , and controlling the reduction of thermal stress can obtain a higher vacancy concentration and reduce the generation of dislocations, thus avoiding the formation of OSF-ring. BRIEF DESCRIPTION OF THE DRAWINGS

[0011] Figure 1It is a schematic diagram of local grid division and heat shield position of the present invention; Figure 2 The C in the silicon single crystal simulated by the two heat shield positions of the present invention v and C i Radial distribution diagram; Figure 3 is the different heat shield positions of the present invention. c Distribution of values DETAILED DESCRIPTION

[0012] In order to make the technical means, creative features, objectives and effects achieved by the present invention easy to understand, the present invention is further explained below in conjunction with specific implementation methods.

[0013] A process for improving oxygen ring defects comprises the following steps: S1: Prepare the single crystal furnace: The single crystal furnace includes carbon felt, quartz crucible, graphite support, melt, heater, heat shield, crystal rod, furnace shell and argon gas pipe; The carbon felt is placed at the bottom of the furnace shell, the graphite holder is located on the top of the carbon felt, the quartz crucible is placed on the top of the graphite holder, the melt is placed in the inner cavity of the quartz crucible, the heater is installed on the outer wall of the quartz crucible, the heat shield is placed in the inner cavity of the quartz crucible, the crystal rod extends to the melt, the argon gas pipe is installed on the side of the furnace shell, and the furnace shell is also equipped with a thickened insulation barrel for reducing the power of seeding and equal diameter, reducing crucible baking, avoiding more oxygen precipitation, and reducing the radial gradient and the thermal stress of the growth interface; S2: Crystal pulling process: Start the heater to heat the quartz crucible. After heating, the crystal rod is combined with the melt for crystal pulling. During the crystal pulling process, the heat shield is controlled to move so that the bottom of the heat shield is away from the melt surface, so that the y value of the crystal increases, which is used to increase the heat radiation area of ​​the side wall of the quartz crucible. The crystal is filled with argon through the argon gas pipe to increase the heating of the lower part of the crystal rod. S3: Set different liquid inlet distances to produce crystal rods for small-batch battery verification, and monitor the OSF generation after the battery topcon high-temperature diffusion heat treatment; S4: performing an oxygen precipitation heat treatment process and a Cu diffusion process on the impurity removal material: the material includes CZ-Si and NCZ-Si, the treated CZ-Si and NCZ-Si are ground with 800 mesh and 2000 mesh SiC particles, and then chemically polished with CP4 solution at 90°C for 30s, and Al with a thickness of 30nm is deposited on the prepared crystal through mask deposition; The treatment of CZ-Si includes oxygen precipitation heat treatment process: 800℃ / 225h, Cu diffusion process: conventional diffusion, 1200℃ / 10min, air cooling; 800℃ / 225h, Cu diffusion process: RTP diffusion, 1200℃ / 50s; 800℃ / 225h+1250℃ / 2h, Cu diffusion process: conventional diffusion, 1200℃ / 10min, air cooling; 750℃ / 16h+1050℃ / 32h, Cu diffusion process: conventional diffusion, 1000℃ / 10min, air cooling; 750℃ / 16h+1050℃ / 32h, Cu diffusion process: conventional Diffusion, 1200℃ / 10min, air cooling; 750℃ / 16h+1050℃ / 32h, Cu diffusion process: RTP diffusion, 1000℃ / 50s, air cooling; 750℃ / 16h+1050℃ / 32h, Cu diffusion process: RTP diffusion, 1000℃ / 100s, air cooling, wherein the treatment of NCZ-Si includes oxygen precipitation heat treatment process: 800℃ / 225h, Cu diffusion process: RTP diffusion, 1200℃ / 50s; 800℃ / 225h+1250℃ / 2h, Cu diffusion process: conventional diffusion, 1200℃ / 10min, air cooling.

[0014] Specifically, embodiment 1: A process for improving oxygen ring defects comprises the following steps: S1: Prepare the single crystal furnace: The single crystal furnace includes carbon felt, quartz crucible, graphite support, melt, heater, heat shield, crystal rod, furnace shell and argon gas pipe; The carbon felt is placed at the bottom of the furnace shell, the graphite holder is located on the top of the carbon felt, the quartz crucible is placed on the top of the graphite holder, the melt is placed in the inner cavity of the quartz crucible, the heater is installed on the outer wall of the quartz crucible, the heat shield is placed in the inner cavity of the quartz crucible, the crystal rod extends to the melt, the argon gas pipe is installed on the side of the furnace shell, and the furnace shell is also equipped with a thickened insulation barrel for reducing the power of seeding and equal diameter, reducing crucible baking, avoiding more oxygen precipitation, and reducing the radial gradient and the thermal stress of the growth interface; S2: Crystal pulling process: Start the heater to heat the quartz crucible. After heating, the crystal rod is combined with the melt for crystal pulling. During the crystal pulling process, the heat shield is controlled to move so that the bottom of the heat shield is away from the melt surface, so that the y value of the crystal increases, which is used to increase the heat radiation area of ​​the side wall of the quartz crucible. The crystal is filled with argon through the argon gas pipe to increase the heating of the lower part of the crystal rod. S3: Set different liquid inlet distances to produce crystal rods for small-batch battery verification, and monitor the OSF generation after the battery topcon high-temperature diffusion heat treatment; S4: performing an oxygen precipitation heat treatment process and a Cu diffusion process on the impurity removal material: the material includes CZ-Si and NCZ-Si, the treated CZ-Si and NCZ-Si are ground with 800 mesh and 2000 mesh SiC particles, and then chemically polished with CP4 solution at 90°C for 30s, and Al with a thickness of 30nm is deposited on the prepared crystal through mask deposition; The treatment of CZ-Si is oxygen precipitation heat treatment process: 800℃ / 225h, Cu diffusion process: conventional diffusion, 1200℃ / 10min, air cooling; the treatment of NCZ-Si is oxygen precipitation heat treatment process: 800℃ / 225h, Cu diffusion process: RTP diffusion, 1200℃ / 50s. Specific embodiment 2: A process for improving oxygen ring defects comprises the following steps: S1: Prepare the single crystal furnace: The single crystal furnace includes carbon felt, quartz crucible, graphite support, melt, heater, heat shield, crystal rod, furnace shell and argon gas pipe; The carbon felt is placed at the bottom of the furnace shell, the graphite holder is located on the top of the carbon felt, the quartz crucible is placed on the top of the graphite holder, the melt is placed in the inner cavity of the quartz crucible, the heater is installed on the outer wall of the quartz crucible, the heat shield is placed in the inner cavity of the quartz crucible, the crystal rod extends to the melt, the argon gas pipe is installed on the side of the furnace shell, and the furnace shell is also equipped with a thickened insulation barrel for reducing the power of seeding and equal diameter, reducing crucible baking, avoiding more oxygen precipitation, and reducing the radial gradient and the thermal stress of the growth interface; S2: Crystal pulling process: Start the heater to heat the quartz crucible. After heating, the crystal rod is combined with the melt for crystal pulling. During the crystal pulling process, the heat shield is controlled to move so that the bottom of the heat shield is away from the melt surface, so that the y value of the crystal increases, which is used to increase the heat radiation area of ​​the side wall of the quartz crucible. The crystal is filled with argon through the argon gas pipe to increase the heating of the lower part of the crystal rod. S3: Set different liquid inlet distances to produce crystal rods for small-batch battery verification, and monitor the OSF generation after the battery topcon high-temperature diffusion heat treatment; S4: performing an oxygen precipitation heat treatment process and a Cu diffusion process on the impurity removal material: the material includes CZ-Si and NCZ-Si, the treated CZ-Si and NCZ-Si are ground with 800 mesh and 2000 mesh SiC particles, and then chemically polished with CP4 solution at 90°C for 30s, and Al with a thickness of 30nm is deposited on the prepared crystal through mask deposition; The treatment of CZ-Si is an oxygen precipitation heat treatment process: 800℃ / 225h, and the Cu diffusion process: RTP diffusion, 1200℃ / 50s. The treatment of NCZ-Si is an oxygen precipitation heat treatment process: 800℃ / 225h, and the Cu diffusion process: RTP diffusion, 1200℃ / 50s. Specific embodiment three: A process for improving oxygen ring defects comprises the following steps: S1: Prepare the single crystal furnace: The single crystal furnace includes carbon felt, quartz crucible, graphite support, melt, heater, heat shield, crystal rod, furnace shell and argon gas pipe; The carbon felt is placed at the bottom of the furnace shell, the graphite holder is located on the top of the carbon felt, the quartz crucible is placed on the top of the graphite holder, the melt is placed in the inner cavity of the quartz crucible, the heater is installed on the outer wall of the quartz crucible, the heat shield is placed in the inner cavity of the quartz crucible, the crystal rod extends to the melt, the argon gas pipe is installed on the side of the furnace shell, and the furnace shell is also equipped with a thickened insulation barrel for reducing the power of seeding and equal diameter, reducing crucible baking, avoiding more oxygen precipitation, and reducing the radial gradient and the thermal stress of the growth interface; S2: Crystal pulling process: Start the heater to heat the quartz crucible. After heating, the crystal rod is combined with the melt for crystal pulling. During the crystal pulling process, the heat shield is controlled to move so that the bottom of the heat shield is away from the melt surface, so that the y value of the crystal increases, which is used to increase the heat radiation area of ​​the side wall of the quartz crucible. The crystal is filled with argon through the argon gas pipe to increase the heating of the lower part of the crystal rod. S3: Set different liquid inlet distances to produce crystal rods for small-batch battery verification, and monitor the OSF generation after the battery topcon high-temperature diffusion heat treatment; S4: performing an oxygen precipitation heat treatment process and a Cu diffusion process on the impurity removal material: the material includes CZ-Si and NCZ-Si, the treated CZ-Si and NCZ-Si are ground with 800 mesh and 2000 mesh SiC particles, and then chemically polished with CP4 solution at 90°C for 30s, and Al with a thickness of 30nm is deposited on the prepared crystal through mask deposition; The treatment of CZ-Si is oxygen precipitation heat treatment process: 800℃ / 225h+1250℃ / 2h, Cu diffusion process: conventional diffusion, 1200℃ / 10min, air cooling, and the treatment of NCZ-Si is oxygen precipitation heat treatment process: 800℃ / 225h, Cu diffusion process: RTP diffusion, 1200℃ / 50s. Specific embodiment four: A process for improving oxygen ring defects comprises the following steps: S1: Prepare the single crystal furnace: The single crystal furnace includes carbon felt, quartz crucible, graphite support, melt, heater, heat shield, crystal rod, furnace shell and argon gas pipe; The carbon felt is placed at the bottom of the furnace shell, the graphite holder is located on the top of the carbon felt, the quartz crucible is placed on the top of the graphite holder, the melt is placed in the inner cavity of the quartz crucible, the heater is installed on the outer wall of the quartz crucible, the heat shield is placed in the inner cavity of the quartz crucible, the crystal rod extends to the melt, the argon gas pipe is installed on the side of the furnace shell, and the furnace shell is also equipped with a thickened insulation barrel for reducing the power of seeding and equal diameter, reducing crucible baking, avoiding more oxygen precipitation, and reducing the radial gradient and the thermal stress of the growth interface; S2: Crystal pulling process: Start the heater to heat the quartz crucible. After heating, the crystal rod is combined with the melt for crystal pulling. During the crystal pulling process, the heat shield is controlled to move so that the bottom of the heat shield is away from the melt surface, so that the y value of the crystal increases, which is used to increase the heat radiation area of ​​the side wall of the quartz crucible. The crystal is filled with argon through the argon gas pipe to increase the heating of the lower part of the crystal rod. S3: Set different liquid inlet distances to produce crystal rods for small-batch battery verification, and monitor the OSF generation after the battery topcon high-temperature diffusion heat treatment; S4: performing an oxygen precipitation heat treatment process and a Cu diffusion process on the impurity removal material: the material includes CZ-Si and NCZ-Si, the treated CZ-Si and NCZ-Si are ground with 800 mesh and 2000 mesh SiC particles, and then chemically polished with CP4 solution at 90°C for 30s, and Al with a thickness of 30nm is deposited on the prepared crystal through mask deposition; The treatment of CZ-Si is oxygen precipitation heat treatment process: 750℃ / 16h+1050℃ / 32h, Cu diffusion process: conventional diffusion, 1000℃ / 10min, air cooling, and the treatment of NCZ-Si is oxygen precipitation heat treatment process: 800℃ / 225h, Cu diffusion process: RTP diffusion, 1200℃ / 50s. Specific embodiment five: A process for improving oxygen ring defects comprises the following steps: S1: Prepare the single crystal furnace: The single crystal furnace includes carbon felt, quartz crucible, graphite support, melt, heater, heat shield, crystal rod, furnace shell and argon gas pipe; The carbon felt is placed at the bottom of the furnace shell, the graphite holder is located on the top of the carbon felt, the quartz crucible is placed on the top of the graphite holder, the melt is placed in the inner cavity of the quartz crucible, the heater is installed on the outer wall of the quartz crucible, the heat shield is placed in the inner cavity of the quartz crucible, the crystal rod extends to the melt, the argon gas pipe is installed on the side of the furnace shell, and the furnace shell is also equipped with a thickened insulation barrel for reducing the power of seeding and equal diameter, reducing crucible baking, avoiding more oxygen precipitation, and reducing the radial gradient and the thermal stress of the growth interface; S2: Crystal pulling process: Start the heater to heat the quartz crucible. After heating, the crystal rod is combined with the melt for crystal pulling. During the crystal pulling process, the heat shield is controlled to move so that the bottom of the heat shield is away from the melt surface, so that the y value of the crystal increases, which is used to increase the heat radiation area of ​​the side wall of the quartz crucible. The crystal is filled with argon through the argon gas pipe to increase the heating of the lower part of the crystal rod. S3: Set different liquid inlet distances to produce crystal rods for small-batch battery verification, and monitor the OSF generation after the battery topcon high-temperature diffusion heat treatment; S4: performing an oxygen precipitation heat treatment process and a Cu diffusion process on the impurity removal material: the material includes CZ-Si and NCZ-Si, the treated CZ-Si and NCZ-Si are ground with 800 mesh and 2000 mesh SiC particles, and then chemically polished with CP4 solution at 90°C for 30s, and Al with a thickness of 30nm is deposited on the prepared crystal through mask deposition; The treatment of CZ-Si includes oxygen precipitation heat treatment process: 750℃ / 16h+1050℃ / 32h, Cu diffusion process: conventional diffusion, 1200℃ / 10min, air cooling, and the treatment of NCZ-Si is: 800℃ / 225h+1250℃ / 2h, Cu diffusion process: conventional diffusion, 1200℃ / 10min, air cooling, like Figure 1 As shown in the figure, when the bottom of the heat shield is away from the melt surface, the y value will increase. On the one hand, as the y value increases, the heat radiation area of ​​the crystal rod from the side wall of the crucible increases. On the other hand, the blowing of argon gas on the solid-liquid interface is weakened, the heating of the lower part of the crystal rod increases, the temperature gradient of the solid-liquid interface decreases, and the thermal stress decreases. like Figure 2 As shown in the figure, when y is equal to 35 and 50, the radial distribution of vacancies and interstitial defects in the crystal rod is that the vacancy concentration gradually decreases, the interstitial concentration gradually increases, and finally intersects at one point or gradually approaches; when the y value is equal to 50mm, the intersection point of vacancies and interstitials becomes farther in the radial direction of the crystal, reducing the generation of self-interstitial silicon atoms, thereby reducing the occurrence of stacking faults and avoiding the generation of OSF; like Figure 3 As shown in the figure, at different heat screen positions, r c Distribution graph of values.

[0019] The process of the present invention is compared with the existing process, wherein specific embodiments 1 to 5 of the process of the present invention are recorded as embodiments 1-5, and the existing process is comparative example 1. The following comparison table is shown: Defect ratio relative value (%) Example 1 9 Example 2 12 Example 3 13 Example 4 11 Example 5 12 Comparative Example 1 110 , it can be seen that the process of the present invention can significantly reduce defects.

[0020] The present invention is a process for reducing the oxidation-induced stacking fault ring of single crystal silicon by adjusting the position of the heat shield. Based on the formation principle of this defect, the solid-liquid interface V / G value is controlled to be greater than the critical value of 0.13 mm during the production process. 2 min -1 k -1 , and controlling the reduction of thermal stress can obtain a higher vacancy concentration and reduce the generation of dislocations, thus avoiding the formation of OSF-ring.

[0021] The above shows and describes the basic principles and main features of the present invention and the advantages of the present invention. It should be understood by those skilled in the art that the present invention is not limited to the above embodiments. The above embodiments and descriptions are only for explaining the principles of the present invention. Without departing from the spirit and scope of the present invention, the present invention may have various changes and improvements, which fall within the scope of the present invention to be protected. The scope of protection of the present invention is defined by the attached claims and their equivalents.

Claims

1. A process for improving oxygen ring defects, characterized in that: The steps include: S1: Prepare single crystal furnace: The single crystal furnace includes carbon felt, quartz crucible, graphite holder, melt, heater, heat shield, crystal rod, furnace shell and argon gas tube; S2: Crystal pulling: The heater is started to heat the quartz crucible. After heating, the crystal ingot is pulled together with the melt. During the crystal pulling process, the heat shield is controlled to move so that the bottom of the heat shield is away from the melt surface, thereby increasing the y value of the crystal and improving the heat radiation area of ​​the side wall of the quartz crucible. The crystal is filled with argon through the argon gas pipe to increase the heating of the lower part of the crystal ingot. S3: Set different liquid nozzle distances to produce crystal ingots for small-batch battery verification, and monitor the OSF generation after the battery topcon high-temperature diffusion heat treatment; S4: The materials for impurity removal are subjected to an oxygen precipitation heat treatment process and a Cu diffusion process: the materials include CZ-Si and NCZ-Si. The treated CZ-Si and NCZ-Si are ground with 800-mesh and 2000-mesh SiC particles, and then chemically polished with CP4 solution at 90°C for 30s. Al with a thickness of 30nm is deposited on the prepared crystal through mask deposition.

2. A process for improving oxygen ring defects according to claim 1, characterized in that: In the step S1, the carbon felt is placed at the bottom of the furnace body shell, the graphite holder is located on the top of the carbon felt, the quartz crucible is placed on the top of the graphite holder, the melt is placed in the inner cavity of the quartz crucible, the heater is installed on the outer wall of the quartz crucible, the heat shield is placed in the inner cavity of the quartz crucible, the crystal rod extends to the melt, the argon gas tube is installed on the side of the furnace body shell, and the furnace body shell is also equipped with a thickened insulation barrel for reducing the seeding and equal-diameter power, reducing crucible baking, avoiding more oxygen precipitation, and reducing the radial gradient and the thermal stress of the growth interface.

3. The process for improving oxygen ring defects according to claim 1, wherein: The treatment of CZ-Si includes oxygen precipitation heat treatment process: 800℃ / 225h, Cu diffusion process: conventional diffusion, 1200℃ / 10min, air cooling; 800℃ / 225h, Cu diffusion process: RTP diffusion, 1200℃ / 50s; 800℃ / 225h+1250℃ / 2h, Cu diffusion process: conventional diffusion, 1200℃ / 10min, air cooling; 750℃ / 16h+1050℃ / 32h, Cu diffusion process Process: Conventional diffusion, 1000℃ / 10min, air cooling; 750℃ / 16h+1050℃ / 32h, Cu diffusion process: Conventional diffusion, 1200℃ / 10min, air cooling; 750℃ / 16h+1050℃ / 32h, Cu diffusion process: RTP diffusion, 1000℃ / 50s, air cooling; 750℃ / 16h+1050℃ / 32h, Cu diffusion process: RTP diffusion, 1000℃ / 100s, air cooling.

4. The process for improving oxygen ring defects according to claim 1, wherein: The treatment of NCZ-Si includes an oxygen precipitation heat treatment process: 800°C / 225h, a Cu diffusion process: RTP diffusion, 1200°C / 50s; 800°C / 225h+1250°C / 2h, a Cu diffusion process: conventional diffusion, 1200°C / 10min, and air cooling.

Citation Information

Cited By

  • In-situ heat treatment method of monocrystalline silicon crystal bar

    CN121381194A